Morphological change of the mouth bar in relation to natural and anthropogenic interferences. (1st March 2019) - He, Yong; Wu, Yao; Lu, Chen; Wu, Menwu; Chen, Ying; Yang, Yugui
Abstract: Mouth bars are important morphological units in deltaic and estuarine systems, which have encountered with significant topography variations driven by anthropogenic interferences and natural forcings. On the basis of seven selected maritime charts covering from 1960s to 2016, we focus on the morphological evolution of mouth bar with bifurcating channels in the Modaomen Estuary, the main fluvially-dominated estuary of the Pearl River Delta. The bar area is relatively in equilibrium with barely aggregation and degradation before 1990 while overall erosion was found thereafter. Sediment volume of the mouth bar between the −2 m and −7 m isobaths drastically decreased after 1990s. Correspondingly, the area of −4 m isobaths of the bar stepwise decreased from about 18 × 10 6 m 2 to 2 × 10 6 m 2, indicating the body of mouth bar above −4 m almost disappeared. The two side channels also suffered significantly morphological evolution. The West Channel (WC) was subjected to uninterrupted erosion. Especially during 2000–2005, the WC below the −2 m isobath experienced remarkable erosion with the increment of water volume reaching 6.7 × 10 6 m 3 . The East Channel (EC) had the potential to expand seaward between 2000 and 2011 yet encountered with accumulation after 2011. Meanwhile, the thalweg of the EC seemed hard to distinguish and the WC displayed more meandering thalweg. Furthermore, Empirical Orthogonal Function was applied to quantify the bathymetric changes with independent modes. The temporal variations of fluvial sediment input displayed significant decreasing trend at MK from 1960 to 2014, which presented a statistically significant relationship with the third mode. However, it only accounts for 13.4% of the overall evolution patterns. Although the remarkable reduction of sediment input generally associates with the degradation in bar area, the sediment load is probably not the primary mechanisms driving morphological changes in the Modaomen Estuary. Anthropogenic interferences including large-scale reclamation and intensive sand excavation should be responsible for the morphological changes. Highlights: Three major evolution patterns of mouth bar are distinguished by Empirical Orthogonal Function analysis. The phase difference of flow between two distributaries relates with the erosion in the West Channel. Morphological changes should be more attributed to anthropogenic disturbances rather than fluvial sediment source.